PENERAPAN MEDIA PAPAN TEMPEL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDN 1 PEUKAN PIDIE - Nasri Diana; Fitria Ulfa (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
This study aims to determine the application of sticky board media can improve the learning outcomes of 3rd grade students of SDN 1 Peukan Pidie. The research design used is the type of classroom action research (CAR) with the Kurt Lewis model. The subjects in this study were class IIIA students of SDN 1 Peukan Pidie, totaling 30 students consisting of 18 male students and 12 female students. Data collection in the study was carried out by observation and tests. The results showed that the average individual score in cycle I was 60.66 with a percentage of 40% of students who completed and 60% of students who did not complete. In cycle II it increased to 68.66% with a percentage of 63.33% of students who completed and 36.33 students who did not complete. And in cycle III it increased again to 79.66 with a percentage of 86.66% of students who completed and 13.33% of students who did not complete. It can be concluded that the application of sticky board media can improve the learning outcomes of class III students of SDN 1 Peukan Pidie.